STUDENTS’ PROBLEMS IN GIVING PRESENTATION A STUDY AT STKIP PGRI OF WEST SUMATERA - Melvina Melvina; Dona Alicia (Universitas Negeri Padang, 2016)
Class presentation is one kinds of activity that is done by the teacher in teaching and learning. In class presentation, the students will present the material or topic that will be discussed in the classroom. In presenting the material, the students get the opportunities to speak English well in their performance. It also gives valuable experience for them to prepare themselves to use English in multi society where English is a demanding tool for communication in our today’s life. This paper is intended to discuss about students’ problem in giving presentation in classroom. The data of this research are collected while teaching and learning process by means of observation, recording, and note taking. The result of the research are, students have some problems in delivering and content of presentation. The result indicates that the students need more practice to improve their speaking performance and take more attention about delivering technique in presentation. While, presentation skill need to be transferred in the classroom by the teacher to prepare students for their further academic career as well as future professional surrounding.